Dynamika i struktura grupy w klasie językowej - Kowal, Iwona (Neofilolog, 2012)
The present paper describes various psycho-social phenomena that occur in groups, in particular in the language classroom. Each group passes through five developmental stages called forming, storming, norming, performing and adjourning. During these phases learners’ behavior and attitudes change, which often leads to conflicts between the teacher and the students. The structure of the group develops in parallel with its dynamics. Students adopt several roles in the group, such as, for example, leader, expert or outsider.